STUDY ON ISOTHERMAL HOT CORROSION RESISTANCE OF AL?.??COCRCUFENI HIGH ENTROPY ALLOYS IN MOLTEN SALT MIXTURE OF NA?SO? AND V?O? AT 1100Â°C - Doras Insani Manalu, Vitasari
The aerospace industry has been identified as a top priority for economic transformation through industrialization. The development of metal alloy industries, particularly for jet engine components like turbine blades, has become critical to support this sector. Nickel-based superalloys have limitations as materials for jet engine turbine blades, necessitating the development of high-entropy alloys. One highly promising alloy is Al0.75CoCrCuFeNi, known for its superior properties for high-temperature applications and predominantly domestic sourcing. Jet engine turbine blades are highly vulnerable to hot corrosion, with the potential to cause catastrophic component failure. This study aims to investigate the hot corrosion resistance of Al0.75CoCrCuFeNi for high-temperature applications in highly corrosive environments, such as jet engine turbine blades. The experiment commenced by melting the alloying elements in a single direct-current electric arc furnace, followed by homogenization at 1100°C for 10 hours using a horizontal tube furnace in an inert environment. The alloy was then cut to produce metal coupons and subjected to isothermal hot corrosion testing in a 50-wt% Na2SO4 + 50-wt% V2O5 molten mixture at 1100°C for 9, 16, 25, and 50 hours. Samples from the hot corrosion tests were characterized using XRD, SEM-EDS, and optical microscopy. The isothermal hot corrosion testing of the Al0.75CoCrCuFeNi alloy in a molten salt mixture of 50-wt% Na2SO4 + 50-wt% V2O5 at 1100°C revealed the formation of Fe3O4, Cu2O, and Al-rich spinel at the early stages of the reaction. Subsequently, Cu2O transformed into the more stable form, CuO. The molten salt and substrate reaction produced AlVO4-V2O5 and Cu2S, while inter-oxide reactions formed various spinel types, such as NiCr2O4, as the alloy tried to form protective layers. Severe spalling and sulfidation were observed during the 50-hour hot corrosion testing. The isothermal hot corrosion kinetics of the Al0.75CoCrCuFeNi alloy in the 50-wt% Na2SO4 + 50-wt% V2O5 molten salt at 1100°C followed a linear trend, described by the equation y = -0.0013x + 238.3177. The hot corrosion mechanism can be divided into four main stages (1) initial oxidation, co-occurring with (2) the dissolution of Al2O3 in the V2O5 melt at the experimental temperature; (3) sulfidation and further oxidation; and (4) basic fluxing.